Addition of a nutraceutical to montelukast or inhaled steroid in the treatment of wheezing during COVID-19 pandemic: a multicenter, open-label, randomized controlled trial. : Recurrent wheezing and treatment. - Parisi, Giuseppe Fabio; Manti, Sara; Papale, Maria; Giallongo, Alessandro; Indolfi, Cristiana; Miraglia del Giudice, Michele; Salpietro, Carmelo; Licari, Amelia; Marseglia, Gian Luigi; Leonardi, Salvatore (Acta Biomedica Atenei Parmensis, 2022)
Background and aim Recurrent wheezing is often triggered by viral respiratory infections. The aims of our study were: i) to evaluate whether the addition of a nutraceutical (Leucodif®), could improve the efficacy of montelukast or inhaled steroids (ICS) compared to the single treatment; ii) to verify whether a treatment is more effective than another. Our study was biased by the COVID-19 pandemic, which resulted in a lockdown of almost two months in Italy. Methods The multicenter, open-label study enrolled 84 children aged 2–6 years diagnosed with recurrent wheezing and randomized them into four treatment arms for three months: ICS treatment; ii) montelukast; iii) montelukast + Leucodif; iv) ICS + Leucodif. Children were assessed at baseline and after one, two, and three months of treatment using the TRACK score for both the caregiver and the physician. Results Out of the 84 patients, 18 patients received ICS therapy, 22 patients ICS + Leucodif, 24 patients montelukast, and 20 patients montelukast + Leucodif. All four treatments resulted in a significant reduction in symptoms with no differences among the various groups. Conclusions Our study demonstrates that montelukast therapy appears to be equally effective as ICS therapy and that the addition of the nutraceutical Leucodif does not appear to improve the treatment outcome. However, in our opinion our study was strongly influenced and biased by the lockdown due to the COVID-19 pandemic, which inherently resulted in reduced exposure to the viruses that commonly cause respiratory infections in children.